Kualitas Digitalisasi Hadis: Analisis SWOT pada Aplikasi OOH - Tajang, Andi Darussalam (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
Facing the digital era and industrial revolution 4.0, the development of the quantity and quality of information services, especially in the development of hadith science in Indonesia is expected to increase significantly in order to reach all communities, especially for people who live in 3T (Terdepan, Tertinggal, Terluar). However, at present the quantity and quality of information technology in the development of hadith science in Indonesia has not been satisfactory, especially by people living in the 3T area. This research, trying to answer the challenges through a SWOT analysis of the One Day One Hadith (OOH) application on the Android operating system. The results of the study show that there are advantages and opportunities that are owned, but there are some weaknesses and threats to be followed up as early as possible in advancing literacy and understanding of Islam, especially in the science of hadith to Muslims in Indonesia.